2018
DOI: 10.5539/gjhs.v10n12p40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Complementary and Alternative Medicine (CAM) Use Among Health Workers in Nigeria

Abstract: BACKGROUND: The use of complimentary and alternative medicines has risen globally. We therefore, explored the prevalence and predictors of use of complementary and alternative medicines among healthcare workers. METHODS: This was a cross-sectional study that was conducted between 1st June and 31st August 2018 on the use of complementary and alternative medicines among health workers in Federal Medical Center Makurdi and Benue State University Teaching Hospital, Makurdi in Benue State. Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A systematic review study showed that the usage rate of CAM ranges from 25 to 96% in nurses. A study in Nigeria showed that the most commonly used modalities of CAM in HP were worship and prayer [ 28 ]. Also, in another study, the most commonly used modalities by HP were massage therapy, non-herbal supplements, and music therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review study showed that the usage rate of CAM ranges from 25 to 96% in nurses. A study in Nigeria showed that the most commonly used modalities of CAM in HP were worship and prayer [ 28 ]. Also, in another study, the most commonly used modalities by HP were massage therapy, non-herbal supplements, and music therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical screening of the hexane, ethyl acetate, and methanol extracts were carried out to determine the presence of the secondary metabolites including alkaloids, saponins, tannins, steroidal compounds, flavonoids, cardiac glycosides, and terpenoids by following the standard procedures [20][21][22][23]. 3)] and rechromatographed using n-hexane alone for the first 10 fractions then hexane: ethyl acetate (19: 1).…”
Section: Preliminary Phytochemical Screeningmentioning
confidence: 99%